2021
DOI: 10.1007/s10488-021-01117-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Emergencies in the Community: Characteristics and Outcome in Switzerland

Abstract: Psychiatric emergencies occur frequently in the community setting, e.g. the patient’s home or public places. Little is known about the characteristics and outcome of these situations. This study describes psychiatric emergencies in the canton of Zurich, Switzerland, and examines determinants of their outcome. We retrospectively analyzed 620 medical records of consultations classified as psychiatric emergencies of a 24/7 service of community-based emergency physicians. Information on sociodemographic, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
0
5
0
7
Order By: Relevance
“…Among the users admitted in different crises, 13.4% required external referral, which evidenced the ability of the services to handle these situations in their own territory. This result is corroborated by international studies, which evidenced that most of the crisis demands in mental health are solved by community services or specialized teams in the community ( 4 , 20 ) . As an example, a study in Switzerland identified 12.7% of referrals for hospitalization ( 20 ) .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Among the users admitted in different crises, 13.4% required external referral, which evidenced the ability of the services to handle these situations in their own territory. This result is corroborated by international studies, which evidenced that most of the crisis demands in mental health are solved by community services or specialized teams in the community ( 4 , 20 ) . As an example, a study in Switzerland identified 12.7% of referrals for hospitalization ( 20 ) .…”
Section: Discussionmentioning
confidence: 58%
“…This result is corroborated by international studies, which evidenced that most of the crisis demands in mental health are solved by community services or specialized teams in the community ( 4 , 20 ) . As an example, a study in Switzerland identified 12.7% of referrals for hospitalization ( 20 ) . We did not find studies that evaluated the CAPS AD III’s ability to handle crises.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Hospital physicians might further benefit from services of consultation- liaison psychiatry in their hospital who have a valid overview on the mental healthcare structures in the region (Evans et al, 2019). Related to emergency physicians, knowledge of HT might be helpful as well to prevent IA in circumstances were outpatient treatment seems to be not sufficient and inpatient treatment is refused by the patient (Mötteli et al, 2021). In addition, patients should also be informed about the HT option (for instance at the beginning of their inpatient treatment through the clinics’ triage team) as most of them do not know the existence of HT services, but have a positive attitude towards this approach.…”
Section: Discussionmentioning
confidence: 99%